2011
DOI: 10.1248/jhs.57.420
|View full text |Cite
|
Sign up to set email alerts
|

Mutanase of Paenibacillus humicus from Fermented Food Has a Potential for Hydrolysis of Biofilms Synthesized by Streptococcus mutans

Abstract: Mutanase is an α-1,3-glucanase that cleaves the α-1,3-glucosidic linkages of glucan polysaccharides termed mutan. There has been interest in mutanase as it has the potential to be considered in preventive medicine. Previously, we identified the mutanase of Paenibacillus humicus from fermented soybeans and observed that the enzyme hydrolyzed insoluble glucans and mutan in vitro. Here we focused on the ability of mutanase in preventing dental caries. We proposed that the enzyme participates in the degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The pH dependence of a-1,3-glucanase HF65 activity was almost similar to those of bacterial a-1,3-glucanases that have been reported to exhibit optimum activity at acidic pH regions (Fuglsang et al, 2000;Imai et al, 1977;Meyer and Phaff, 1980;Pleszczy¢ nska et al, 2010;Shimotsuura et al, 2008;Suyotha et al, 2014;Tsumori et al, 2011). The effect of temperature was also investigated in the range 30-80∞C (Fig.…”
Section: Fig 1 Sds-pagesupporting
confidence: 68%
See 2 more Smart Citations
“…The pH dependence of a-1,3-glucanase HF65 activity was almost similar to those of bacterial a-1,3-glucanases that have been reported to exhibit optimum activity at acidic pH regions (Fuglsang et al, 2000;Imai et al, 1977;Meyer and Phaff, 1980;Pleszczy¢ nska et al, 2010;Shimotsuura et al, 2008;Suyotha et al, 2014;Tsumori et al, 2011). The effect of temperature was also investigated in the range 30-80∞C (Fig.…”
Section: Fig 1 Sds-pagesupporting
confidence: 68%
“…Thus, the enzyme is of interest due to its potential use in the removal of dental plaque and the biological control of pathogenic fungi. Some studies have demonstrated the ability of a-1,3-glucanases to reduce the plaque synthesized by Streptococcus species, as well as to inhibit plaque formation (Fuglsang et al, 2000;Pleszczy¢ nska et al, 2010;Shimotsuura et al, 2008;Tsumori et al, 2011;Wiater et al, 2004Wiater et al, , 2008. Moreover, they indicated that the degradation of plaque by the enzyme was more effectively performed in combination with dextranase (Fuglsang et al, 2000;Shimotsuura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insoluble glucan-biofilms were generated using S. mutans 10449 (ATCC; absorbance of 0.05 at 600 nm, at the middle logarithm stages) in 96-well microplates (Corning, NY, USA; Tsumori et al, 2011). S. mutans supplemented with 100 µL of Todd Hewitt Broth (Invitrogen, Carlsbad, CA, USA), 50 µL of 1.0% sucrose, and 50 µL of increasing amounts of naked nisin (0.1-100 pmol) in 10 mM sodium citrate buffer (pH = 5.0) were placed in each well and incubated for 1 h at 37°C.…”
Section: Assay Of Effects Of Nisin and Nisin-liposome On Insoluble Glmentioning
confidence: 99%
“…Insoluble glucans in each well were washed with 10 mM sodium phosphate buffer (pH = 7.0) and suspended in 0.2 mL of 1.0 M sodium hydroxide. Alkali-soluble glucans were recovered and glucose levels quantified as glucan-biofilms by the phenol-sulfuric acid method (Tsumori et al, 2011).…”
Section: Assay Of Effects Of Nisin and Nisin-liposome On Insoluble Glmentioning
confidence: 99%